Implementation of Character Education for Students and The Role of the Nyai in Developing the Al-Inayah Cebolek Kidul Islamic Boarding School - Evi Ziadaturrohmah; Yusuf Falaq (JURNAL PENDIDIKAN IPS, 2023)
Bu Nyai's role in developing the Al-Inayah Cebolek Kidul Islamic boarding school is very important, from its inception until now. Al-Inayah Islamic boarding school is one of the tahfidzul qur'an Islamic boarding schools in Cebolek Kidul village. Character education for students is also very important to overcome moral crises and strengthen character. The aim of this research is to determine the implementation of Santri Character Education and the role of Mrs. Nyai in developing the Al-Inayah Cebolek Kidul Islamic Boarding School. This study uses a qualitative method. This research was carried out very selectively to obtain the authenticity of the data. The results of this research can be concluded as follows: (1) The aim of Islamic boarding school education is to develop and create a personality that is in harmony with Islamic teachings. (2) Islamic boarding schools are educational institutions with unique characteristics. Character education has an important role in maintaining good character throughout his life. (3) Mrs. Nyai Hj. Musyarofah has made a major contribution to the development of Pondok Al-Inayah from its inception until now. In the domestic realm, Mrs. Nyai often chases the students about cleanliness, discipline, and being unclean and pure. Meanwhile, in the public sphere, Bu Nyai often holds routine Koran readings every Saturday and Wednesday with the women of the Cebolek Kidul village.